(untitled) (Journal of Telenursing (JOTING), 2020)
This study aims to determine the effect of diabetes exercise on reducing blood glucose levels in people with diabetes. This type of research is a quasi-experimental design non-equivalent control group design with a simple case study approach. A case study conducted in 5 days for 30 minutes showed that Diabetes Gymnastics was effective in reducing blood sugar levels in people with Diabetes Mellitus by 7.1%. In conclusion, diabetes exercises conducted for five consecutive days, effectively lower blood glucose levels in people with diabetes. Keywords: Diabetes Mellitus, Blood Sugar, Gymnastics